Письма М. О. Гершензона к А. В. Звенигородскому [Mikhail Gershenzon’s Letters to Andrei Zvenigorodsky] - Sobolev, Alexander (Slavica Revalensia, 2018)
This article is a prefaced and extensively contextualized publication of 27 letters from Mikhail Gershenzon (1869—1925) to an obscure Russian Symbolist poet Andrei Zvenigorodsky (1878—1961) written from June 25, 1904 to April 11, 1917. In the preface section of the article, special attention is paid to some circumstances related to their mutual research interest, the legacy of Petr Chaadaev (1894—1856).